Effect of lateral extra-articular tenodesis on the rate of revision anterior cruciate ligament reconstruction in elite athletes - Borque, K. A.; Jones, M.; Laughlin, M. S.; Balendra, G.; Willinger, L.; Pinheiro, V. H.; Williams, A. (The American Journal of Sports Medicine, 2022)
Background: There is growing evidence that anterolateral procedures can reduce the risk of rerupture in high-risk recreational athletes undergoing primary anterior cruciate ligament (ACL) reconstruction (ACLR). However, this effectiveness has never been evaluated in elite athletes.